A pesca e o conhecimento tradicional dos pescadores de um lago de inundação no Baixo Amazonas: sugestões para manejo e conservação - SERRÃO, Elizabete de Matos (Universidade Federal do Oeste do Pará, 2021)
This work aimed to analyze the traditional knowledge of fishermen about reproduction, feeding, habitat and behavior of the main fish species, as well as to describe socioeconomic aspects, fishing characteristics and the current situation of fishery resources, and to analyze the environmental perception of fishermen in identification of conflicts / problems in the region in order to gather subsidies to contribute to the management policies of the fishing resources of the region and that may be useful in the elaboration of the APA-Maicá management plan, helping to propose important strategies for the management, conservation and sustainability of the species and maintenance of the local fishing activity. Data were collected between march and december 2017 through semi-structured forms applied directly to fishermen associated with Fishermen's Colony and Fishermen Z-20 or who live in the communities and / or neighborhoods that are inserted in the proposed area for the implementation of APA-Maicá or are linked to one of the four existing Core Units in the area. For the ethno-ecological analysis, we interviewed 88 fishermen who had ten or more years of fishing experience in the region. Fishermen's knowledge was consistent, detailed and consistent with the scientific literature. The fishermen indicated the size of the first sexual maturity of the fish, information that added to the biology and reproduction of the species is extremely important in the formulation of measures of adequate fishing management to the region. It was also reported a diversity of items used in fish feed, in addition to the numerous habitats used by the species, which suggests the great dependence of the fish for this environment, either as a place of food, shelter or reproduction. A total of 96 fishermen were interviewed to characterize fishing activity, socioeconomic profile and environmental perception. The fishing activity in the Maicá region is presented as smallscale and artisanal, with the use of relatively simple equipment, with emphasis on the gillnet, preferably in motorized canoes and oars for the capture of 32 categories of fish. The main fishing site is the lake and its surroundings, used in all the seasonal periods, with predominance in the moments of full and ebb of the local hydrological cycle, proving itself as a relevant ecosystem and an important means of subsistence for these communities and / or neighborhoods that develop in their surroundings, being one of the main sources of occupation, food, subsistence and income. Fishermen's perception shows that they understand and have a broad environmental vision with awareness of the problems affecting the environment in which they live, such as the marked decrease in fish caused by actions of anthropic origin, among which of fishery that involves different actors), overfishing, deforestation and lack of inspection, as well as the socio-environmental conflicts existing in the region, always showing concern for the future of fishing in the region, which led to the suggestion of mitigating measures, such as APAMaicá regulations. These results reinforce the importance of the incorporation of the traditional knowledge of the fishermen in the management plans, as well as the use of the relevant information of the socioeconomic components and of the fishing activity that must be used to measure the response of the fishing industry to the proposed management system.